Peningkatan Kualitas Produk Lulur Varian Lidah Buaya di UD. Sekar Jagat Dengan Metode Quality Function Deployment (QFD) - Giri, Ni Kadek Ayu Savitri; Wiranatha, Anak Agung Putu Agung Suryawan; Yoga, I Wayan Gede Sedana (Department of Agroindustrial Technology, Faculty of Agricultural Technology, Udayana University, 2024)
Aloe vera scrub is a body treatment that comes from the natural ingredient aloe vera which is known to have moisturizing benefits for the skin. This research aims to determine the attributes that consumers consider important for the aloe vera variant of the Sekar Jagat scrub product, analyze the level of importance and consumer satisfaction with the quality of the Aloe Vera variant of the Sekar Jagat scrub product and formulate a priority strategy for improving the quality of the Aloe Vera variant of the Sekar Jagat scrub. This research analysis uses the Quality Function Deployment method. Determination of sample size in this study used non-probability sampling techniques. The number of samples used in this research was 80 respondents. Based on the research that has been conducted, there are 10 consumer interest attributes, with the highest importance value being aroma (4.49) and the lowest being the price attribute (4.23). The attribute that has the lowest satisfaction value is information on the packaging (3.14). The strategy that can be recommended to improve product quality is that the company needs to evaluate the attributes that have the highest priority for improvement based on the improvement ratio, namely the information attributes on the packaging, packaging size and content. The company needs to evaluate the technical parameters that have priority for improvement based on the level value. technical interests, namely determining the formula, mixing and secondary packaging. With a deep understanding of consumer needs and preferences, as well as implementing effective marketing strategies, the company has the potential to strengthen its position in the market and increase sales of its products in the future